Pengaruh Shoot Training Terhadap Akurasi Shooting Punggung Kaki Pada Permainan Futsal: Vilipus Pinis, Mohamad Sabransyah - pinis, vilipus (Journal Sport Academy, 2024)
This research aims to determine the effect of shoot training on the accuracy of instep shooting in futsal games (experimental study of extracurricular students at SMA Negeri 1 Sungai Ambawang, Kuburaya Regency). The research method used in this research is the experimental method. The data collection techniques used are tests and measurements. The data collection tool used is a Shooting test at a target on a futsal playing field that has been marked and numbered. The population in this study were futsal extracurricular students, a sample of 20 students. The sample selected for this research were extracurricular students at SMA Negeri 1 Sungai Ambawang, Kuburaya Regency. Based on the results of the t-test, the calculated t_value is 12,150 > t_table 2,093 and the sig (2-Tailed) value is .000 < 0.05, so H_o is rejected and Ha is accepted. The magnitude of the increase in kick accuracy can be seen from the difference in the average value, which is 4.90. Thus, it can be concluded that there is an influence of shoot training on instep shooting accuracy in futsal games (experimental study of extracurricular students at SMA Negeri 1 Sungai Ambawang, Kuburaya Regency).